Tracing New Landscapes in the Arena of Nanoparticle-Based Cancer Immunotherapy - Nadukkandy, Aisha Shigna; Ganjoo, Eshani; Singh, Ankit; Dinesh Kumar, Lekha (Frontiers in Nanotechnology, 2022)
Over the past two decades, unique and comprehensive cancer treatment has ushered new hope in the holistic management of the disease. Cancer immunotherapy, which harnesses the immune system of the patient to attack the cancer cells in a targeted manner, scores over others by being less debilitating compared to the existing treatment strategies. Significant advancements in the knowledge of immune surveillance in the last few decades have led to the development of several types of immune therapy like monoclonal antibodies, cancer vaccines, immune checkpoint inhibitors, T-cell transfer therapy or adoptive cell therapy (ACT) and immune system modulators. Intensive research has established cancer immunotherapy to be a safe and effective method for improving survival and the quality of a patient’s life. However, numerous issues with respect to site-specific delivery, resistance to immunotherapy, and escape of cancer cells from immune responses, need to be addressed for expanding and utilizing this therapy as a regular mode in the clinical treatment. Development in the field of nanotechnology has augmented the therapeutic efficiency of treatment modalities of immunotherapy. Nanocarriers could be used as vehicles because of their advantages such as increased surface areas, targeted delivery, controlled surface and release chemistry, enhanced permeation and retention effect, etc. They could enhance the function of immune cells by incorporating immunomodulatory agents that influence the tumor microenvironment, thus enabling antitumor immunity. Robust validation of the combined effect of nanotechnology and immunotherapy techniques in the clinics has paved the way for a better treatment option for cancer than the already existing procedures such as chemotherapy and radiotherapy. In this review, we discuss the current applications of nanoparticles in the development of ‘smart’ cancer immunotherapeutic agents like ACT, cancer vaccines, monoclonal antibodies, their site-specific delivery, and modulation of other endogenous immune cells. We also highlight the immense possibilities of using nanotechnology to accomplish leveraging the coordinated and adaptive immune system of a patient to tackle the complexity of treating unique disease conditions and provide future prospects in the field of cancer immunotherapy.